Impact of Diabetic Retinopathy on Health-related Quality of Life in Iranian Diabetics - Cyrus ALINIA; Seyed-Farzad MOHAMMADI; Alireza LASHAY; Arash RASHIDIAN (Iranian Journal of Public Health, 2017)
Background: To extract utility values of diabetic retinopathy on a perfect health and perfect vision scales for Iranians with both types diabetes.